The Efficacy of Different Plant Extracts Against Whitefly Bemisia tabaci (Aleyrodidae: Hemiptera) on A Tomato Plant: Different Plants Extracts Use Against-Whitefly (Biological Sciences - PJSIR, 2024)
Whitefly (Bemisia tabaci) is a well known pest of many crops specially vegetables including tomato plant. Mostly tomato plant disorders are directly and indirectly related to the silver leaf whitefly (Bemisia tabaci) feeding. In this manner, most countries use lots of pesticides which are really threatening to the environment and ecosystem at an alarming position. Thus we aim to use different plant extracts to control whitefly efficiently and minimize the negative impact of pesticides on the environment. This experiment was conducted in a greenhouse and field as well to draw complete conclusion. In this experiment we used five different treatments, T1-NLE (neem leaves extracts), T2-TLE (tobacco leaves extracts), T3- combination (TLE+NLE+ neem kernels), T4-insecticide (Movento) and T5-un-treated. According to our findings in the greenhouse, adult whitefly population's lowest count is (0.66±0.248) in NLE treated tomato plants and highest whitefly numbers found were (5.84±1.04) in un-treated plants. For the nymph, the same result follows (0.23±0.20) in NLE treated plants and (5.62±1.20) in un-treated plants. In field's experiment lowest adult population of whitefly found in NLE (1.74±0.48) and highest numbers found in un-treated (9.64±1.23). This experiment proves that plants extracts are more effective, economical and eco-friendly. This study can be potentially extended to other pests and crops. Consolidated viewpoint of this investigation, we state that plants extricates all the more integral assets to control sucking complex or whitefly.